2021
DOI: 10.1002/jmv.27309
|View full text |Cite
|
Sign up to set email alerts
|

Post‐acute COVID‐19 syndrome (PCS) and health‐related quality of life (HRQoL)—A systematic review and meta‐analysis

Abstract: There is an established literature on the symptoms and complications of COVID-19 but the after-effects of COVID-19 are not well understood with few studies reporting persistent symptoms and quality of life. We aim to evaluate the pooled prevalence of poor quality of life in post-acute COVID-19 syndrome (PCS) and conducted meta-regression to evaluate the effects of persistent symptoms and intensive care unit (ICU) admission on the poor quality of life. We extracted data from observational studies describing per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

33
336
6
23

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 419 publications
(489 citation statements)
references
References 35 publications
(115 reference statements)
33
336
6
23
Order By: Relevance
“…Regarding the impact of ICU admission in the development of persisting symptoms, contradictory results have been reported up to now 21 , 22 . In our study, we did not find any relationship between ICU admission and the persistence of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the impact of ICU admission in the development of persisting symptoms, contradictory results have been reported up to now 21 , 22 . In our study, we did not find any relationship between ICU admission and the persistence of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, our knowledge on the relationship between QoL and CD in long-COVID-19 is limited. For instance, the relationship between QoL and long-COVID-19 has so far been characterized from the perspective of patient characteristics, rather than the persistence of symptoms [35]. In this case, a meta-regression analysis of seven studies shows that poor QoL measured via self-reports was significantly higher among individuals post-COVID-19 who reported persistent fatigue, but not CD [35].…”
Section: Introductionmentioning
confidence: 99%
“…Since COVID-19 vaccination still does not reach everyone (not even all people with a compelling indication to be vaccinated), and because there are still some uncertainties regarding the long-term immunity and the protection against new variants [6], the study of individuals at risk of severe adverse outcomes from COVID-19, including hospitalization, admission to an intensive care unit (ICU), intubation or mechanical ventilation, or death [7], continues to be of major importance, in order to prioritize this group for vaccination or to shield them from the rest of the population [8]. More recently, the literature has shown that post-COVID-19 patients can suffer from several sequelae [9], and among those with a previous ICU admission, their quality of life is poorer [10].…”
Section: Introductionmentioning
confidence: 99%